Air pollution is associated with faster cognitive decline in Alzheimer's disease - Young‐gun Lee; Seon‐Jin Yoon; So Hoon Yoon; Sung Woo Kang; Seun Jeon; Minseok Kim; Dong Ah Shin; Chung Mo Nam; Byoung Seok Ye (Annals of Clinical and Translational Neurology, 2023)
Abstract Objective Although chronic exposure to air pollution is associated with an increased risk of dementia in normal elderlies, the effect of chronic exposure to air pollution on the rates of cognitive decline in Alzheimer's disease (AD) has not been elucidated. Methods In this longitudinal study, a total of 269 patients with mild cognitive impairment or early dementia due to AD with the evidence of brain β‐amyloid deposition were followed‐up for a mean period of 4 years. Five‐year normalized hourly cumulative exposure value of each air pollutant, such as carbon monoxide (CO), nitrogen dioxide (NO2), sulfur dioxide (SO2), and particulate matter (PM2.5 and PM10), was computed based on nationwide air pollution database. The effects of chronic exposure to air pollution on longitudinal cognitive decline rate were evaluated using linear mixed models. Results Higher chronic exposure to SO2 was associated with a faster decline in memory score, whereas chronic exposure to CO, NO2, and PM10 were not associated with the rate of cognitive decline. Higher chronic exposure to PM2.5 was associated with a faster decline in visuospatial score in apolipoprotein E ε4 carriers. These effects remained significant even after adjusting for potential confounders. Interpretation Our findings suggest that chronic exposure to SO2 and PM2.5 is associated with faster clinical progression in AD.